Assessing the Burden of Infant Deaths Due to Herpes Simplex Virus, Human Immunodeficiency Virus, and Congenital Syphilis: United States, 1995 to 2017. (August 2021) - Slutsker, Jennifer Sanderson; Schillinger, Julia A.
Abstract : Background: Despite advances in diagnosis and treatment, neonatal infection with herpes simplex virus (HSV) has a high case fatality rate. The national burden of neonatal HSV and associated deaths is unknown because this condition is not nationally notifiable. We investigated trends in HSV-related infant deaths compared with infant deaths from congenital syphilis (CS) and human immunodeficiency virus (HIV). Methods: Linked birth-death files for infant deaths from 1995 to 2017 were obtained from the National Center for Health Statistics. These files include infants who were born alive and died in the first 365 days of life and exclude stillbirths. We searched death certificates for disease codes indicating HSV, CS, or HIV, and calculated the frequency and rate of deaths for each infection, overall, by infant sex, and birthing parent age and race/ethnicity. Results: Nationally, 1591 deaths related to the infections of interest were identified: 1271 related to HSV (79.9%), 234 to HIV (14.7%), and 86 to CS (5.4%). Herpes simplex virus–related deaths increased significantly from 0.83/100, 000 live births (95% confidence interval [CI], 0.57–1.17) in 1995 to 1.77 (95% CI, 1.37–2.24) in 2017. In contrast, HIV-related deaths declined: 1.64/100, 000 (95% CI, 1.27–2.10) in 1995 to 0.00 in 2017. There was a median of 3 CS-related deaths/year, with elevated frequencies in 1995 to 1996 and 2017 (n = 8). Herpes simplex virus–related death rates were elevated among infants born to birthing parents younger than 20 years (4.17/100, 000; 95% CI, 3.75–4.59) and to Black parents (2.86/100, 000; 95% CI, 2.58–3.15). Conclusions: Nationally, HSV-related infant deaths exceeded those caused by HIV and CS and seem to be increasing. Our findings underscore the need for an effective HSV vaccine, test technologies enabling rapid identification of infants exposed to HSV at delivery, and a focus on equity in prevention efforts. Abstract : Infant deaths related to herpes infection are increasing in the United States and significantly exceed those related to other perinatal infections. Improvements in prevention and detection are urgently needed.